Lambeaux autofermants pour le traitement des brulures electriques du scalp par haut voltage - Hafidi, J. (Euro-Mediterranean Council for Burns and Fire Disasters - MBC, 2011)
Electrical burns caused by high voltage are responsible for extensive tissue damage. This damage continues in the days following the accident because of the heat deriving from the Joule effect and vascular microthrombosis. In such cases of destruction of the periostum and the calvarium we use coverage flaps. From June 1997 to June 2008, 15 patients were treated for loss of scalp substance due to high-voltage electric burns. The loss, in the tonsural region and varying in size from 9 to 11 cm, was reliably covered per primam in the first week following the accident using axial and multiple coverage flaps. We report the experience of the Division of Plastic Surgery, Ibn-Sina, Rabat, Morocco.